Integrated advertising, promotion, and marketing communications - Clow, Kenneth E. (Pearson Prentice Hall, 2007)
Using a hands-on approach, this text shows students how to develop a complete integrated marketing communications programme. It incorporates Internet exercises and a 'Building an IMC Campaign' project, with free 'Advertising Plan Pro' software